Exploration of the Role of Tiktok Content: Influencer Strategy, Affiliate Marketing, and Online Customer Reviews in Influencing Generation Z Purchasing Decisions at Shopee - F Fitria; Desi Tia Adisti; D Dea; Agum Gumelar; Adi Setiawan (Athena: Journal of Social, Culture and Society, 2024)
This study aims to determine the effect of the role of influencers, affiliate marketing, and online customer reviews at Shopee through TikTok content on Generation Z purchasing decisions. This research uses a quantitative approach by collecting data through an online survey of 199 respondents of the Management Study Program students class of 2020. The data were analyzed using multiple regression methods to evaluate the relationship between the independent variables of influencer roles, affiliate marketing, and online customer reviews and the dependent variable (purchasing decisions). The analysis results show that the role of influencers, affiliate marketing, and online customer reviews have a positive and significant influence on Generation Z's purchasing decisions. The findings emphasize the importance of integrating marketing strategies through influencers, affiliate marketing, and online customer reviews in influencing Generation Z's purchasing decisions. This provides guidance for businesses to utilize e-commerce platforms such as Shopee and TikTok content as an effective means of communication to reach and influence the Generation Z market. This research makes a new contribution to the understanding of how the role of influencers, affiliate marketing and online customer reviews on Shopee, particularly through TikTok content, can influence Generation Z's purchasing decisions. This research adds insight into effective marketing strategies to capture the attention and influence the consumption behavior of the younger generation in the context of e-commerce platforms.